PENENTUAN PRIORITAS PERBAIKAN PELAYANAN MENGGUNAKAN METODE KANO DAN QFD (Studi Kasus PT. Perawang Kencana Motor) - Dedi Dermawan; Denur Jumali (Jurnal Teknik Industri Terintegrasi, 2019)
This research was conducted at the PT. Perawang Kencana Motor. The problems faced today are consumers who are still not satisfied with the services provided by PT. Perawang Kencana Motor, caused by complaints from consumers. The method used in this study is the Kano Method with Quality Function Deployment (QFD). The tools used are House Of Quality (HOQ). This study aims to determine customer expectations, determine the categories of customer needs that are mapped into the Kano method, and determine improvement proposals based on existing technical responses to services provided by PT. Perawang Kencana Motor, so that service users of PT. Perawang Kencana Motor can feel a better level of service satisfaction. From the results of data processing obtained 15 variable consumer expectations that become priority improvements to achieve customer satisfaction PT. Perawang Kencana Motor. Furthermore, from the results of processing the canoe model, Atrractive categories were obtained as many as 5 attributes, namely the suitability of prices with the results received, mechanics must be adept at handling motor damage, employee skills in explaining the products to be sold, the availability of complete spare parts, and the existence of wifi facilities, the One Dimentional category 3 attributes, namely the comfort of the waiting room in the workshop area, uniform clothing, and mechanical responses motorcycle maintenance consultancy,indifferet category 2 attributes, namely ease of payment and cleanliness of the showroom area. Therefore, the authors provide a proposal that was developed from the results of the analysis of technical responses.